Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1136/bcr-2021-247672
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of valve regurgitation due to cancer-related non-bacterial thrombotic endocarditis after switching direct oral anticoagulation for heparin

Abstract: Non-bacterial thrombotic endocarditis (NBTE) is a rare condition related to a state of hypercoagulability in advanced neoplastic disease. Most of the time, arterial thromboembolic event precedes the diagnosis of NBTE. We report here a case of NBTE responsible for multiple ischaemic strokes, which leads to the diagnosis of metastatic pancreatic adenocarcinoma. Aortic and mitral valvular regurgitations secondary to NBTE appeared within 6 weeks despite therapeutic anticoagulation with direct oral anticoagulant (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“… 9 NOACs have not been evaluated and seem inefficient as reported by some case reports in the literature. 12 , 13 , 14 , 15 …”
Section: Discussionmentioning
confidence: 99%
“… 9 NOACs have not been evaluated and seem inefficient as reported by some case reports in the literature. 12 , 13 , 14 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…Newer studies have suggested that heparin or LWMH would be preferred in cases of malignancy-associated NBTE, while Vitamin K antagonists (VKA) agonists like warfarin may be preferred in antiphospholipid syndrome-associated NBTE 5 6. Multiple recent cases documented the failure of DOACs in treating NBTE 7–9. No studies have compared the efficacy of different anticoagulation strategies for NBTE to date.…”
Section: Discussionmentioning
confidence: 99%
“…5 Case report recent cases the failure of DOACs in treating NBTE. [7][8][9] No studies have compared the efficacy of different anticoagulation strategies for NBTE to date. A prospective multicentre trial is required to study the efficacy of the various anticoagulant regimens for NBTE, and whether these therapies should be tailored for patients with versus without underlying malignancy.…”
Section: Outcome and Follow-upmentioning
confidence: 99%